A reconfigurable switching diode loaded patch antenna for S, C, X, Ku, and K bands applications - Shuriji, Mushreq Abdulhussain; Thaher, Raad Hamdan (Institute of Advanced Engineering and Science, 2024)
A reconfigurable patch loaded via a switching radio frequency (RF) diode has been designed, investigated, and fabricated. The fabricated microstrip is able to adjust among several frequencies. A spectrum analyzer is used to test and measure different modes of operations. The proposed antenna is offered a new solution of uncomplicated and incomplex design via eliminating the biasing circuit while maintaining the finest performance. Two fast-switching diodes have been inserted as a new electrical reconfiguration technique. Thus, the suggested antenna is skilled to function in different bands. An ultra-small size antenna of 31×21 mm2 has offered various operating frequencies such as S-band at 2.4 GHz, C-band at 4.97 GHz, 5.06 GHz, 5.18 GHz, 5.1 GHz, and 7.94 GHz, X-band at 10.73 GHz, 10.91 GHz, and 11.9 GHz, Ku-band at 13.52 GHz, 14.78 GHz, 14.97 GHz, 15.63 GHz, 16.4 GHz, 17.3 GHz, and 17.48 GHz, and K-band at 19 GHz. The manufactured reconfigurable patch antenna is proficient for several wireless technologies for instance industrial scientific medical band (ISM): Bluetooth, wireless-fidelity (Wi-Fi), ZigBee, internet of things (IoT), WiMAX, and smart power meters. Also, long term evolution (LTE), 5G applications, fixed wireless systems (FWS), and satellite communication applications.